A Study of Automatic Pineapple Leaf Fibre Extraction Machine Using Bidirectional Rolling Mechanism - Nguyen, Van-Tinh; Ngoc-Kien Nguyen (International Journal of Integrated Engineering, 2024)
Pineapple leaf fibres are well known around the world due to the good material properties when woven together and environment friendly. Nevertheless, it takes a lot of effort and time to extract the fibres from the pineapple leaves. Consequently, various machines have been constructed around the world to automate this process, which has helped save time and increased the output productivity remarkably. This paper proposed a novel design of the automatic pineapple leaf fibre extraction machine using bidirectional rolling mechanism. The proposed mechanism will improve the efficiency of the pineapple leaf fibre extraction process that simultaneously enhances the quality of the output fibres.